On Their Own: Women, Urbanization, and the Right to the City in South Africa - Wong, Yen Nee (Atlantis, 2017)
The essay reviews Allison Goebal’s gendered analysis of women's 'right to the city' in post-apartheid South Africa and concludes that the work makes a crucial contribution to the scholarship in its injection of a 'politics of difference' and a gendered lens. The book would however benefit from expanding on its discussion of women's care burdens to explore the inclusion of care on African women's experience of justice in the city.